A Hierarchical Collision Detection Algorithm for VA - Meiping Wu; Liyun Shi; Zhijun Ren (2010 Chinese Control and Decision Conference, 2010)
This paper presents a Hierarchical Collision Detection Algorithm that is suitable for VA (Virtual Assembly). The proposed algorithm includes three level approaches which are preliminary detection, second detection and precision detection. The surround box approach was used for the preliminary detection, which can preclude a lot of detached part, and the detection quantity was reduced greatly. If two parts may collide or interfere, then, calculate the intersection region and storage the result in surround box S. The vector judgment approach was used to the second detection, which can reduce the half calculation working. The net-facet approach was utilized for the precision detection, which can quick calculate the opposite location of two parts. If they intersect we can get the intersection measure, otherwise, the nearest point or minimum distance between them can be got. By the algorithm, the calculation speed and detection accuracy are improved greatly and thereby can help in creation of the optimal assembly sequence quickly in virtual assembly environment.